2019
DOI: 10.1097/nnr.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A and Chronic Stress in Pregnant Women at 24–28 Weeks Gestation

Abstract: Background: Allostatic Load (AL) is a biopsychosocial model that suggests chronic psychosocial stress leads to physiologic dysregulation and poor outcomes. The purpose of this study was to examine AL in pregnant women operationalized using pro-inflammatory cytokines and psychosocial indicators and perinatal outcomes. Objectives: In pregnant women, identify relationships between circulating cytokines/ chemokines and the Prenatal Distress Questionnaire (PDQ), Maternal Antenatal Attachment Scale (MAAS), Emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A panel of plasma anti‐inflammatory (interleukin [IL]‐10, IL‐4, IL‐1 receptor antagonist [RA]) and pro‐inflammatory (IL‐6, IL‐8, tumour necrosis factor‐alpha [TNF‐α], IL‐1β, IL‐17A, monocyte chemoattractant protein (MCP)‐1) cytokines and chemokines will be quantified using a custom Bio‐Plex multiplex immunoassay (Bio‐Rad; Hercules, CA), which uses Luminex xMAP technology (Luminex Corp; Austin, TX) and has been successfully used for the quantification of cytokines and chemokines in neonatal peripheral blood (Carlo et al, ; Matoba et al, ). The pro‐inflammatory cytokines and chemokines were selected for their previously demonstrated effects on the adult and infant brain (Jain & Mills, ), neurodevelopment (Kinjo et al, ; O'Shea et al, ), or association with chronic stress exposure (Moore et al, ). The anti‐inflammatory factors were selected for their regulating effects on IL‐1β, IL‐6, IL‐8, MCP‐1, and TNF‐α (Moore, de Waal Malefyt, Coffman, & O'Garra, ) and importance in higher cognitive function (Gadani, Cronk, Norris, & Kipnis, ).…”
Section: The Studymentioning
confidence: 99%
“…A panel of plasma anti‐inflammatory (interleukin [IL]‐10, IL‐4, IL‐1 receptor antagonist [RA]) and pro‐inflammatory (IL‐6, IL‐8, tumour necrosis factor‐alpha [TNF‐α], IL‐1β, IL‐17A, monocyte chemoattractant protein (MCP)‐1) cytokines and chemokines will be quantified using a custom Bio‐Plex multiplex immunoassay (Bio‐Rad; Hercules, CA), which uses Luminex xMAP technology (Luminex Corp; Austin, TX) and has been successfully used for the quantification of cytokines and chemokines in neonatal peripheral blood (Carlo et al, ; Matoba et al, ). The pro‐inflammatory cytokines and chemokines were selected for their previously demonstrated effects on the adult and infant brain (Jain & Mills, ), neurodevelopment (Kinjo et al, ; O'Shea et al, ), or association with chronic stress exposure (Moore et al, ). The anti‐inflammatory factors were selected for their regulating effects on IL‐1β, IL‐6, IL‐8, MCP‐1, and TNF‐α (Moore, de Waal Malefyt, Coffman, & O'Garra, ) and importance in higher cognitive function (Gadani, Cronk, Norris, & Kipnis, ).…”
Section: The Studymentioning
confidence: 99%
“…Foram encontrados estudos dos seguintes países Turquia (n=4), Coréia do Sul (n=2), Finlândia (n=1), Chile (n=1), Estados Unidos (n=1), Inglaterra (n=1), Polônia (n=1) e Brasil (n=1), evidenciando escassez de pesquisas no território nacional. & Güneri, 2020;Mackie et al , 2020;Moore et al, 2019;Souza et al, 2022;Topan et al, 2022), dois tiveram como objetivo verificar a capacidade preditiva de determinados fatores na intensidade do AMF (Kucharska, 2020;Yoon & Sung, 2021), três compararam grupos de gestantes de alto e baixo risco (Dagla et al, 2022;Palma et al, 2020;Yesilcinar et al, 2023) promoção do AMF (Baltacı & Başer, 2022;Jussila et al, 2021;Kim & Chun, 2020).…”
Section: Resultsunclassified
“…After enrollment, blood samples for the quantification of cytokines were collected weekly until infants reached 35 weeks PMA. We selected cytokines for the parent study based on their reported associations with neurodevelopment in preterm infants (Nist & Pickler, 2019), stress (Moore et al, 2019), or brain development (Gadani et al, 2012).…”
Section: Methodsmentioning
confidence: 99%